Obra Nueva de la Institución Educativa: José Joaquín Flórez Hernández - Gaitán Valderrama, Pedro Andrés (Universidad Antonio Nariño, 2022)
The city of Ibague is the most populated territory in the department of Tolima; 85% of public schools in the city have inefficient infrastructures and lack of spaces for entertainment or recreation for students in the region. The José Joaquin Flores Hernández Educational Institution was chosen as the new construction project. Located on the second most populated commune of the city that according to the diagnosis elaborated in this thesis, it was determined that it presents the greatest deficiency in educational establishments.